2020
DOI: 10.2147/cia.s256070
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cerebral Thrombolysis in Rural Residents Aged ≥ 80</p>

Abstract: The proportion of older people in Poland is higher in rural areas than in urban areas. Thus, we aimed to evaluate treatment rate and factors associated with outcome and safety of intravenous thrombolysis (IVT) in rural residents aged ≥80 years admitted to primary stroke centers. Patients and Methods: This study was a retrospective, observational cohort study of 873 patients treated with recombinant tissue plasminogen activator (rt-PA) in primary stroke centers between February 1, 2009 and December 31, 2017. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The data in the present study show a less favorable evolution among elderly people undergoing reperfusion but no increase in mortality rates. Sobolewski et al (2020) suggested that patients aged ≥80 may be safely treated with cerebral reperfusion in routine practice. The results of this Latin American cohort study also reaffirm the benefits of thrombolytic therapy for stroke patients in this age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data in the present study show a less favorable evolution among elderly people undergoing reperfusion but no increase in mortality rates. Sobolewski et al (2020) suggested that patients aged ≥80 may be safely treated with cerebral reperfusion in routine practice. The results of this Latin American cohort study also reaffirm the benefits of thrombolytic therapy for stroke patients in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Sobolewski et al ( 2020 ) suggested that patients aged ≥80 may be safely treated with cerebral reperfusion in routine practice. The results of this Latin American cohort study also reaffirm the benefits of thrombolytic therapy for stroke patients in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients aged 80 or more who had mRS 3-6 90 days after stroke onset (n = 53) compared to those with favourable outcome (n = 49) had higher NIHSS score on admission (16 [14-20] vs. 7 [5][6][7][8][9][10][11][12], p < 0.001) and after IVT (15 [8][9][10][11][12][13][14][15][16][17][18] vs. 2 [1-6], p < 0.001), more often had haemorrhagic brain complications after IVT (35.85% vs. 8.16%, p < 0.001) and premorbid disability (pre-stroke mRS score ≥ 1: 28.30% vs. 8.16%, p = 0.010), less often had fasting glucose level below 5.5 mmol/L (9.43% vs. 26.53%, p = 0.023), had higher CRP levels (27.2 [9.1-84.1] vs. 4.3 [2.1-10.3] mg/L, p < 0.001), and had higher maximal diastolic blood pressure within 24 hours after IVT (80 [72-90] vs. 80 [70-85] mmHg, p = 0.026) (Supplemental Tab. 1).…”
Section: Determinants Of Favourable Outcomementioning
confidence: 99%
“…1). Patients below 60 who had mRS 3-6 90 days after stroke onset (n = 10) compared to those with a favourable outcome (n = 59) more often suffered from hypertension (90.00% vs. 54.24%, p = 0.033), more often underwent MT (90.00% vs. 38.98%, p = 0.028), had higher NIHSS score on admission (19 [18-20] vs. 9 [5][6][7][8][9][10][11][12][13][14][15][16], p = 0.005) and after IVT (19 [15][16][17][18][19] vs. 4 [2][3][4][5][6][7][8], p < 0.001), more often had haemorrhagic brain complications after IVT (70.00% vs. 14.56%, p < 0.001), and had higher CRP levels (9.3 [7.2-14.0] vs. 4.0 [1.5-7.7] mg/L, p = 0.018) (Supplemental Tab. 1).…”
Section: Determinants Of Favourable Outcomementioning
confidence: 99%
See 1 more Smart Citation